Kajian Learning Obstacle pada Topik Aljabar ditinjau dari Literasi Matematis oleh PISA 2021 - Hidayah, Yumna; Sudihartinih, Eyus; Sumiaty, Encum (Jurnal Pendidikan Matematika RAFA, 2021)
The purpose of this study is to determine the type of Learning Obstacle (LO) on the topic of Algebra in terms of Mathematical Literacy by PISA 2021. The method used in this research is a qualitative method using a didactical design research framework that focuses on learning obstacles. The instrument used in studying learning obstacles was designed based on the mathematical literacy of PISA 2021. The participants of this study came from the city of Cirebon, which consisted of four junior high school students in class IX, one high school student in class X, and two high school students in class XI. Data were collected through written tests, interviews, and observations. The results of this study are four types of learning obstacles, namely related to difficulties in converting story questions into mathematical modeling, lack of mastery of the application of algebra in the form of story questions, difficulties in converting story questions into geometric models and ignorance and confusion about what to do in completing test instruments which is given.